Substantial secondary organic aerosol formation in a coniferous forest: observations of both day- and nighttime chemistry - Lee, Alex K. Y.; Abbatt, Jonathan P. D.; Leaitch, W. Richard; Li, Shao-Meng; Sjostedt, Steve J.; Wentzell, Jeremy J. B.; Liggio, John; Macdonald, Anne Marie (ATMOSPHERIC CHEMISTRY AND PHYSICS, 2016)
Substantial biogenic secondary organic aerosol (BSOA) formation was investigated in a coniferous forest mountain region in Whistler, British Columbia. A largely biogenic aerosol growth episode was observed, providing a unique opportunity to investigate BSOA formation chemistry in a forested environment with limited influence from anthropogenic emissions. Positive matrix factorization of aerosol mass spectrometry (AMS) measurement identified two types of BSOA (BSOA-1 and BSOA-2), which were primarily generated by gas-phase oxidation of monoterpenes and perhaps sesquiterpenes. The temporal variations of BSOA-1 and BSOA-2 can be explained by gas-particle partitioning in response to ambient temperature and the relative importance of different oxidation mechanisms between day and night. While BSOA-1 arises from gas-phase ozonolysis and nitrate radical chemistry at night, BSOA-2 is likely less volatile than BSOA-1 and consists of products formed via gas-phase oxidation by OH radical and ozone during the day. Organic nitrates produced through nitrate radical chemistry can account for 22-33aEuro-% of BSOA-1 mass at night. The mass spectra of BSOA-1 and BSOA-2 have higher values of the mass fraction of m/zaEuro-91 (f(91)) compared to the background organic aerosol. Using f(91) to evaluate BSOA formation pathways in this unpolluted, forested region, heterogeneous oxidation of BSOA-1 is a minor production pathway of BSOA-2.